Clinical effective observation of different controlled ovarian hyperstimulation stimulation schemes on infertility patients with poor ovarian reserve in IVF/ICSI-ET - Du, Hang; Wang, Meixian; Shi, Yanbin; Zhang, Ruihong; Zhang, Fan; Bai, Tingting; Cong, Shuyan; Shao, Xiaoguang; Zhang, Jie (Serican Journal of Medicine, 2024)
Objective: Patients with poor ovarian reserve usually present with both high cancellation rates in stimulation ovulation cycles and low live birth rates, which represent the important clinical challenges in in vitro fertilization. Our study aimed to investigate optimal ovarian stimulation via retrospective clinical analysis of pregnancy outcomes achieved by in vitro fertilization/intracytoplasmic sperm injection-embryo transfer（IVF/ICSI-ET) with multiple stimulation schemes in poor ovarian reserves (PORs). Materials and methods: In this study, we compared 5 regimens for POR patients undergoing IVF/ICSI in Dalian Women and Children’s Medical group and Affiliated Zhongshan hospital of Dalian University, Dalian, China, from January 2021 to October 2024 according to POSEIDON criteria. Patients were classified into progestin-primed ovarian stimulation（PPOS), modified natural, corpus luteum, GnRH-antagonist and minor stimulation groups. Clinical analytic indexes including rates of retrieved oocytes, embryos, fresh embryo transfer cycles and pregnancy were the main outcomes. Results: Comparing with the other groups, GnRH-antagonist group resulted with higher Gonadotrophin duration, Gonadotrophin dosage, number of oocytes retrieved and fertilized oocytes. Better clinical outcomes consist of higher rates of oocytes retrieved, transferrable embryos,fresh embryo transfer cycles, embryo implantation, pregnancy were obtained in GnRH-antagonist group. Modified natural group and minor stimulation group has lower oocytes retrieved number, the startup dose and total amount of Gn is smaller, and the Gn use is shorter, which leads to a decrease in the number of antral follicles, and thus reducing the number of oocytes retrieved and available embryos. Conclusion: The duration and total dose of Gn stimulation were longer and higher in the GnRH-antagonists，but also provided more retrieved oocytes, preferential oocytes. Further more，in fresh embryo transfer，GnRH-antagonists are associated with higher clinical pregnancy.